Spongionella Secondary Metabolites, Promising Modulators of Immune Response through CD147 Receptor Modulation - Sánchez, Jon Andoni (Front Immunol, 2016)
The modulation of the immune system can have multiple applications such as cancer treatment, and a wide type of processes involving inflammation where the potent chemotactic agent cyclophilin A (Cyp A) is implicated. The Porifera phylum, in which Spongionella is encompassed, is the main producer of marine bioactive compounds. Four secondary metabolites obtained from Spongionella (Gracilin H, A, L, and Tetrahydroaplysulphurin-1) were described to hit Cyp A and to block the release of inflammation mediators. Based on these results, some role of Spongionella compounds on other steps of the signaling pathway mediated by this chemotactic agent can be hypothesized. In the present paper, we studied the effect of these four compounds on the surface membrane CD147 receptor expression, on the extracellular levels of Cyp A and on the ability to migrate of concanavalin (Con A)-activated T lymphocytes. Similar to a well-known immunosuppressive agent cyclosporine A (CsA), Gracilin H, A, L, and tetrahydroaplysulphurin-1 were able to reduce the CD147 membrane expression and to block the release of Cyp A to the medium. Besides, by using Cyp A as chemotactic agent, T cell migration was inhibited when cells were previously incubated with Gracilin A and Gracilin L. These positive results lead us to test the in vivo effect of Gracilin H and L in a mouse ear delayed hypersensitive reaction. Thus, both compounds efficiently reduce the ear swelling as well as the inflammatory cell infiltration. These results provide more evidences for their potential therapeutic application in immune-related diseases of Spongionella compounds.